FUNGSI SASTRA LISAN â€œTANDUKâ€ MASYARAKAT GENAHARJO KABUPATEN TUBAN BAGI MASYARAKAT PENDUKUNGNYA - Suantoko, Suantoko (Universitas Pendidikan Indonesia, 2016)
AbstractÂ This study aims to investigate the function of â€œtandukâ€ oral literature for its society. In this case, the people in question are society Genaharjo of Tuban district. Through the use of the theory of functions Alan Dundes and William R. Bascom, it is understood that the â€œtandukâ€ has a function of oral literature that focuses as the teaching and interdependence among societies that emphasize the benefits of practicality. â€œTandukâ€ oral literature function is the function of propaganda, the function of social solidarity and an antidote to individualism, and the function of education in the socialization of values. The overall function of shaping identity in order to establish harmony in social life.Keywords: function, Genaharjo society, tanduk oral literature